A History of Plastic Surgery - Santoni-Rugiu, Paolo; Sykes, Philip J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
Dear Readers, Cosmetic Surgery (Chapters12–15). Te frst section deals with anatomy and the healing of wounds, discusses You have in your hands a work that should become a old and new plastic surgical procedures, and outlines the milestone of our understanding of medical history. In it history of anaesthesia. Te second covers the methods Professor Paolo Santoni-Rugiu and Mr Philip Sykes trace used from ancient times to reconstruct various areas of the development of plastic surgery and much of medi- the body and is the most extensive. Te last section d- cine in general, over three millennia. With his extensive cusses the history of cosmetic surgery and the origin of knowledge of clinical plastic surgery, no one could be present day procedures. better placed than the senior author to gather this valu- Te pages ring with the names of giants of the medical able material from historical documents. As well as us- sciences such as Hippocrates, Leonardo da Vinci, W- ing the great historical libraries of Italy, the authors were liam Harvey and Iginio Tansini, to say nothing of plastic able to refer to the many books in the Sanvenero-Ros- surgeons from the nineteenth and twentieth centuries.
The Anatomical Foundations of Surgery -- Healing of Wounds and the Development of Surgery -- Skin Flaps -- Skin Grafts -- Grafts of Other Tissues -- Some Notes on Anaesthesia -- Nasal Reconstruction -- Cleft Lip and Palate -- Reconstruction of the External Genitalia -- Ear Reconstruction -- Skull Reconstruction -- to Cosmetic Surgery -- Cosmetic Rhinoplasty -- Facial Rejuvenation -- Cosmetic Surgery of the Breast.
Keywords: Plastic surgery; Surgery; Traumatology; Plastic Surgery; Surgery; Traumatic Surgery